BACE-1 is expressed in the blood–brain barrier endothelium and is upregulated in a murine model of Alzheimer's disease. Issue 7 (July 2016) - Devraj, Kavi; Poznanovic, Slobodan; Spahn, Christoph; Schwall, Gerhard; Harter, Patrick N; Mittelbronn, Michel; Antoniello, Katia; Paganetti, Paolo; Muhs, Andreas; Heilemann, Mike; Hawkins, Richard A; Schrattenholz, André; et al.
Endothelial cells of the blood–brain barrier form a structural and functional barrier maintaining brain homeostasis via paracellular tight junctions and specific transporters such as P-glycoprotein. The blood–brain barrier is responsible for negligible bioavailability of many neuroprotective drugs. In Alzheimer's disease, current treatment approaches include inhibitors of BACE-1 (β-site of amyloid precursor protein cleaving enzyme), a proteinase generating neurotoxic β-amyloid. It is known that BACE-1 is highly expressed in endosomes and membranes of neurons and glia. We now provide evidence that BACE-1 is expressed in blood–brain barrier endothelial cells of human, mouse, and bovine origin. We further show its predominant membrane localization by 3D- d STORM super-resolution microscopy, and by biochemical fractionation that further shows an abluminal distribution of BACE-1 in brain microvessels. We confirm its functionality in processing APP in primary mouse brain endothelial cells. In an Alzheimer's disease mouse model we show that BACE-1 is upregulated at the blood–brain barrier compared to healthy controls. We therefore suggest a critical role for BACE-1 at the blood–brain barrier in β-amyloid generation and in vascular aspects of Alzheimer's disease, particularly in the development of cerebral amyloid angiopathy.